Nanoscale Tubular Vessels for Storage of Methane at Ambient Temperatures - Kowalczyk, Poitr; Solarz, L.; Do, D.; Samborski, A.; MacElroy, J. (American Chemical Society, 2006)
Novel carbon nanostructures can serve as effective storage media for methane, a source of “clean energy” for the future. We have used Grand Canonical Monte Carlo Simulation for the modeling of methane storage at 293 K and pressures up to 80 MPa in idealized bundles of (10,10) armchair-type single-walled carbon nanotubes and wormlike carbon pores. We have found that these carbon nanomaterials can be treated as the world’s smallest high-capacity methane storage vessels. Our simulation results indicate that such novel carbon nanostructures can reach a high volumetric energy storage, exceeding the US FreedomCAR Partnership target of 2010 (5.4 MJ dm-3), at low to moderate pressures ranging from 1 to 7 MPa at 293 K. On the contrary, in the absence of these nanomaterials, methane needs to be compressed to approximately 13 MPa at 293 K to achieve the same target. The light carbon membranes composed of bundles of single-walled carbon nanotubes or wormlike pores efficiently physisorb methane at low to moderate pressures at 293 K, which we believe should be particularly important for automobiles and stationary devices. However, above 15-20 MPa at 293 K, all investigated samples of novel carbon nanomaterials are not as effective when compared with compression alone since the stored volumetric energy and power saturate at values below those of the bulk, compressed fluid.